HBeAg seroconversion is associated with a more effective PD-L1 blockade during chronic hepatitis B infection - Sara Ferrando-Martinez; Kelly Huang; Angie Snell Bennett; Patricia Sterba; Li Yu; JoAnn A. Suzich; Harry L.A. Janssen; Scott H. Robbins (JHEP Reports, 2019)
Background & Aims: Current therapies for chronic hepatitis B virus (HBV) infection control viral replication but do not eliminate the risk of progression to hepatocellular carcinoma. HBV-specific CD8 T cells are necessary for viral control, but they are rare and exhausted during chronic infection. Preclinical studies have shown that blockade of the PD-1:PD-L1 axis can restore HBV-specific T cell functionality. The aim of this study was to analyze how the clinical and treatment status of patients impacts the ability of HBV-specific T cells to respond to PD-L1 blockade. Methods: Expression patterns of the PD-1:PD-L1/PD-L2 axis were analyzed in healthy donors and chronically infected patients in different clinical phases of disease. A functional assay was performed to quantify baseline HBV-specific T cell responses in chronically infected patients. Baseline responses were then compared to those attained in the presence of an anti-PD-L1 monoclonal antibody (MEDI2790). Results: Chronically infected patients were characterized by the upregulation of PD-1 within the T cell compartment and a concomitant upregulation of PD-L1 on myeloid dendritic cells. The upregulation was maximal in HBV e antigen (HBeAg)-positive patients but persisted after HBeAg negativization and was not restored by long-term treatment. HBV reactivity, measured as frequency of HBV-specific T cells, was significantly higher in HBeAg-negative patients with lower HBV DNA levels, independently of HBV surface antigen or alanine aminotransferase levels. Anti-PD-L1 blockade with MEDI2790 increased both the number of IFN-γ-producing T cells and the amount of IFN-γ produced per cell in 97% of patients with detectable HBV reactivity, independently of patients’ clinical or treatment status. Conclusion: Patients with lower levels of HBV DNA and the absence of HBeAg have more intact HBV-specific T cell immunity and may benefit the most from PD-L1 blockade as a monotherapy. Lay summary: Hepatitis B virus (HBV)-specific T cell responses during chronic infection are weak due to the upregulation of inhibitor molecules on the immune cells. In this study we show that the inhibitory PD-1:PD-L1 axis is upregulated during chronic HBV infection and successful antiretroviral therapy does not restore normal levels of PD-1 and PD-L1 expression. However, in HBV e antigen-negative patients, treatment with an anti-PD-L1 antibody can increase the functionality of HBV-specific T cell responses by an average of 2-fold and is a promising new therapy for patients with chronic HBV infection. Keywords: Chronic HBV infection, PD-L1 blockade, PD-1 blockade, HBV-specific T cells, checkpoint inhibitor, immunotherapy, MEDI2790, HBV cure